Saudi Arabian Short Story Thresholds: A Semiotic Study of Selected Works from 2018-2019 - Al-Shamari, Nuf Salim (Arts for Linguistic & Literary Studies, 2023)
This study aims to examine the textual thresholds in a number of short stories published by the Saudi Literature, Publishing, and Translation Authority in the period between 2018 and 2019. Adopting a semiotic approach, the study analyzes these thresholds, each distinguished by its unique composition and structure, exploring their implications and meanings, and illustrating how each threshold interacts with the narrative it is associated with. The study is divided into an introduction (focusing on the concept of thresholds in semiotic approach terms), and two sections. The first section examined the external thresholds, including the front and back covers with their illustrations, icons, colors, titles, and promotional phrases. The second section dealt with the significant internal thresholds manifested in the titles of the selected short stories, excluding other internal thresholds. The study concluded that the thresholds varied in terms of their form and meanings, reflecting the Saudi environment with its diverse cultural and geographical components.